Effects of Nano additives on performance and emission characteristics of Mentha longifolia biodiesel. Issue 3 (23rd February 2020) - Ganesan, S.; Mahalingam, S.; Shyam Daniel Raj, R. Arul; Rajesh, S.
ABSTRACT: Sustainable development of natural resources in this technological world goes hand in hand with the issues like cleaner environment, plantation of oil providing trees, etc. The overall objective of the national mission is to increase the creation of national infrastructure for production of biodiesel through cultivation of Jatropha plant and processing of its oil. Therefore, the objective of this paper is to provide a clean economical solution to this problem. The use of biodiesel leads to reduction in NO x, HC, CO2 and CO, and increase in fuel consumption on diesel engine. The present diesel engine. The Nano particles were dispersed in the biodiesel. If the additives added in the biodiesel at appropriate proportion, it will helpful to increase the engine combustion and performance characteristics. Nano-additives reduce the fuel consumption and improve the thermal efficiency during combustion additives release the energy to the fuel. The current Investigation is to study the effect of Nano-fuel additives cerium oxide (CeO2 ) the performance and emission characteristics of Mentha longifolia biodiesel in a single cylinder, four stroke.